ENGLISH TEACHERS’ STRATEGIES IN MANAGING LARGE CLASSES: A CASE STUDY - Siti Safura; Cut Mawar Helmanda; Afra Ninda (English Education and Applied Linguistics Journal (EEAL Journal), 2023)
In order to create an engaging teaching and learning environment, classroom management is crucial for teachers. In line with this, this study was to find out the teachers’ way in managing large classes and to know what strategies that used by the teachers when teaching the large classes. The design of this study is qualitative method. This study involved two English teachers at MTsN 3 Banda Aceh. The data of this study were collected through observation and interview. To analyze the data, Miles and Huberman’ concepts was applied. The finding of this study demonstrated that that the teachers of MTsN 3 Banda Aceh managed large class by applying the proper strategies to ease at teaching and controlling large number of students effectively. The implemented strategies by teachers included (1) planning the lesson plan; (2) creating the comfortable classroom; (3) grouping students and forcing discussion; and (4) making rules and providing learning media.